STUDI PERBANYAKAN ENDOMIKORIZA INDIGENUS HASIL ISOLASI DARI PERKEBUNAN KOPI ARABIKA DI KECAMATAN KINTAMANI, BALI, DENGAN PEMBERIAN STRES AIR DAN MEDIA TUMBUH BERBEDA - I Gusti Ayu Kadek Dian Permatha Suyoga; I Nyoman Rai; I Wayan Wiraatmaja (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Coffee is very important agro industry in Bali Province. The coffee center in Bali which is already famous for its geographic indication protection status is Kintamani District, which is the largest producer of Arabica coffee and an icon of Arabica coffee in Bali. Therefore, efforts are needed to maintain coffee production through the selection of fertilizers that do not harm the environment, for example biological fertilizers derived from arbuscular mycorrhizal fungi (AMF). This study aimed to find the best growing media composition and optimal soil water content and the interaction between the two treatments for endomycorrhizal spore propagation. This research was arranged in a completely randomized design (CRD) with 2 factors and 4 replications. The first factor was composition of growing media which consisted of four levels, i.e. Mt (soil only), Mp (soil and volcanic sand with ratio of 1:1/v:v), Mk (soil and compost with ratio of 1:1/v:v), and Mc (soil, volcanic sand, and compost with ratio of 1:1:1/v:v:v). The second factor was water stress which consisted of three levels, i.e. A0 (100% field capacity), A1 (70% field capacity), and A2 (40% field capacity). The highest spore multiplication results were obtained in the combination treatment of MpA0 as much as 55,00 spores with an increase of 120%. Meanwhile the combination treatment of MkA2 produced the lowest spores as much as 34.25 spores with an increase of 37%.